Internal Control and Financial Accountability in Non-Tax Forest Revenue Management: A Qualitative Study - Elis Nur Aisyah; Dwi Martani (Balance : Jurnal Akuntansi dan Bisnis, 2025)
This study critically examines the internal control system over Non-Tax State Revenue (PNBP) derived from forest area utilization within the Directorate General of Forest Area Planning and Establishment of Forest Management Areas (RPKHPWPH) under the Ministry of Forestry. The performance audit by the Supreme Audit Agency (BPK) reported that the internal control over PNBP for Forest Area Utilization still requires further evaluation. Drawing on a qualitative approach based on descriptive analysis, observation, interviews, and field observations, this research reveals shortcomings in monitoring, evaluation, and documentation. Several necessary improvements in the internal control system for PNBP PKH at the Directorate of RPKHPWPH encompass improving a culture of control, risk mitigation, implementing stricter policies, enhancing transparency, adopting a preventive approach, and engaging stakeholders to achieve organizational objectives efficiently. Recommendations to enhance the internal control system for PNBP PKH include the necessity for initiatives to foster a culture of control, robust risk mitigation, high transparency, preventive approaches, stakeholder involvement, and better monitoring.